Similarities between two-part sentences in Chinese and Kazakh languages (Journal of Oriental Studies, 2018)
In this article we comprehensively conducted similarities betweentwo-part sentences in Chinese and Kazakh language. According to thethinking of Chinese people the order of thought is determined like: doer ofthe action + action + receiver of the action. In accordance with grammar:the subject + the predicate + the object. According to the thinking of Kazakhpeople the order of thought is determined like: doer of the action+receiver of the action + action. In accordance with grammar: the subject+ the object + the predicate. Also, other similarities were researched inthis article.